2022
DOI: 10.1200/jco.2022.40.16_suppl.4073
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic artery infusion chemotherapy (HAIC) combined with sintilimab and bevacizumab biosimilar (IBI305) for initial unresectable hepatocellular carcinoma (HCC): A prospective, single-arm phase II trial.

Abstract: 4073 Background: Sintilimab plus IBI305, a bevacizumab biosimilar, showed a significant overall survival and progression-free survival benefit versus sorafenib in the first-line setting for patients with unresectable hepatocellular carcinoma. Hepatic arterial infusion chemotherapy is an intraarterial procedure that has been widely used in Asia, with high response rate. This trial was designed to assess the feasibility and efficacy of HAIC combined with sintilimab and IBI305 in advanced unresectable hepatocell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The results showed that 20 of the 30 subjects enrolled in the HAIC-S-IBI305 study were evaluated as PR according to mRECIST criteria, with an ORR of 66.7%. 37 The 29 participants enrolled in the TRIPLET study had an ORR of 70.96% and 87.10% based on RECIST v1.1 and mRECIST, respectively, and an mPFS of 10.80 months based on mRECIST. 38 A single-arm, Phase II study investigating the safety and assessing the efficacy of SBRT combined with sintilimab in patients with oligometastatic hepatocellular carcinoma was reported at the 2022 ASCO Annual Meeting.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that 20 of the 30 subjects enrolled in the HAIC-S-IBI305 study were evaluated as PR according to mRECIST criteria, with an ORR of 66.7%. 37 The 29 participants enrolled in the TRIPLET study had an ORR of 70.96% and 87.10% based on RECIST v1.1 and mRECIST, respectively, and an mPFS of 10.80 months based on mRECIST. 38 A single-arm, Phase II study investigating the safety and assessing the efficacy of SBRT combined with sintilimab in patients with oligometastatic hepatocellular carcinoma was reported at the 2022 ASCO Annual Meeting.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy is a recommended choice of maintenance therapy. [1,2] Durvalumab was the first immune checkpoint inhibitor to demonstrate a positive impact on mPFS as a potential maintenance therapy in surgery-ineligible NSCLC, but OS data remained to be determined. [27] Pembrolizumab could prolong the mOS to 15.9 months when maintained for 35 cycles in patients with squamous NSCLC with PD-L1 expression ≥ 1% who received pembrolizumab plus chemotherapy as first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the unavailability of effective combined immunotherapy and the concerns over the safety profile of induction chemotherapy, treatment options remain constrained for patients with locally advanced or metastatic non-small cell lung cancer (NSCLC) lacking sensitive gene mutations. [1][2][3][4][5][6] Within this therapeutic landscape, maintenance therapy has emerged as a strategy to enhance prognosis in patients with advanced NSCLC following chemotherapy. [7][8][9][10][11][12] Anlotinib, a novel, orally administered tyrosine kinase inhibitor (TKI), targets a spectrum of receptor tyrosine kinases (RTKs), including vascular endothelial growth factor receptor (VEGFR), fibroblast growth factor receptor (FGFR), platelet-derived growth factor receptor (PDGFR), and c-kit, thereby inhibiting tumor angiogenesis and growth.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent advances in immunotherapy have led to a re-evaluation of the value of systemic therapy in the conversion therapy setting. A series of phase II and phase III trials have evaluated the feasibility and effectiveness of ICIs and their combinations for conversion therapy [ 151 153 ] (NCT05056337, NCT05738616). However, the expected value of conversion therapy in terms of improving survival is primarily based on small-sample cohort and retrospective studies, and further evidence is still needed to validate and optimize the conversion therapy strategy.…”
Section: The Roles Of Immunotherapy-based Perioperative Treatment In Hccmentioning
confidence: 99%